2018
DOI: 10.1111/ele.12934
|View full text |Cite
|
Sign up to set email alerts
|

Neighbour tolerance, not suppression, provides competitive advantage to non‐native plants

Abstract: High competitive ability has often been invoked as a key determinant of invasion success and ecological impacts of non-native plants. Yet our understanding of the strategies that non-natives use to gain competitive dominance remains limited. Particularly, it remains unknown whether the two non-mutually exclusive competitive strategies, neighbour suppression and neighbour tolerance, are equally important for the competitive advantage of non-native plants. Here, we analyse data from 192 peer-reviewed studies on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
60
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 118 publications
2
60
4
Order By: Relevance
“…On average, alien species were not more competitive than native species. Therefore, our results contradict those of two recent meta‐analyses which found that alien species were more competitive than native species (Kuebbing & Nunez ; Golivets & Wallin ). However, in the two meta‐analyses, approximately 90% of the alien species were invasive plants.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…On average, alien species were not more competitive than native species. Therefore, our results contradict those of two recent meta‐analyses which found that alien species were more competitive than native species (Kuebbing & Nunez ; Golivets & Wallin ). However, in the two meta‐analyses, approximately 90% of the alien species were invasive plants.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to the results of two recent meta‐analyses, which found that alien species experienced weaker strength of interspecific competition than native species (Kuebbing & Nunez ; Golivets & Wallin ), we found no significant difference in interspecific competition experienced by native and alien species. Possibly, although we measured interspecific competition with a more accurate approach (i.e.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations